Im Fahrwasser des Sonnengottes : Eine Studie zum Darreichen der Morgen- und Abendbarke in den ägyptischen Tempeln griechisch-römischer Zeit. - Kertmann, Jessica (Studien zur spätägyptischen Religion., 2020)
The journeys of the sun god in his barges along the sky and through the underworld are among the central elements of the ancient Egyptian world view. The ideas associated with the course of the sun were described and presented in more or less detail in different text genres in the course of Egyptian religious history. In the temples of the Greco-Roman period, 45 examples of a type of ritual scene are attested, showing the king offering the morning and evening bark to the sun god. Jessica Kertmann places these scenes at the center of her study. In the first part of the study, the testimonies are presented in an annotated translation, in which the position in the temple, the structure of the scene and the iconography of the barges are also discussed. Building on this, the second part is followed by an analysis of the scenes and their texts from various points of view. The conception of the individual protagonists and their iconography are taken into account as well as the counter-gifts, the sun's course motifs and the formal design of the scene texts. The study is supplemented by an overarching chapter on the conception of the course of the sun and the sun barques as well as the question of the new assignment of the barques to the phases of the day in Greco-Roman times.